Legal Considerations Regarding Child As Victim Of Abuse Decision Sexual On Verdict Number 9/Jn/2023/ Ms.Tkn - Safiah, Cut Siti; Hotnidah; Fitriyani, Fitriyani (Institut Agama Islam Negeri Kendari, 2025)
The studies aim to explain how the judge's considerations decide the punishment of 72 months imprisonment for the accused in decision Number 9/JN/2023/ MS.Tkn. and how the judge's considerations are based on the theory of Justice and aspects of Child Protection. This research use type of study with a method approach normative and library research. The materials law in study shared become two namely material Primary law includes decisions court Number 9/JN/2023/ MS.Tkn, Law Child Protection, Qanun and materials law secondary includes; publication books, journals, articles law, thesis, dissertation, related with abuse sexual in children. Data collection techniques are carried out with the method to study decision Number 9/JN/2023/ MS.Tkn with access to the Directory site Decision Supreme Court using the keyword “ harassment” sexual ” and legal writing others. Data analysis techniques used are descriptive analytic use do analysis to Decision Court Sharia Takengon Number 9/JN/2023/ MS.Tkn. Research results show that the judge's consideration to dropping the punishment prison of 72 months for the Defendant based on the testimony of witnesses and the fulfillment of elements Article 47 of Aceh Qanun Number 6 of 2014. Considerations If seen from glasses, Justice procedural is Already fulfilled, but Not yet fully reflect Justice substantive for the victims. In line with the matter, That aspect of protecting children for the victims is also not yet fully fulfilled. The judge did not consider the history of the past crimes​ defendant, and the judge did not prioritise recovery impact psychological towards victims such as rehabilitation or restitution. The judge only focuses on the criminalisation of the perpetrator without the existence affirmation mechanism of protection and recovery child as a victim.